Pain Severity Correlates With Biopsy-Mediated Colonic Afferent Activation But Not Psychological Scores in Patients With IBS-D. Issue 2 (22nd February 2021) - Cibert-Goton, Vincent; Lam, Ching; Lingaya, Melanie; Falcone, Yirga; Wood, John N.; Bulmer, David C.; Spiller, Robin
Abstract : INTRODUCTION: Despite heterogeneity, an increased prevalence of psychological comorbidity and an altered pronociceptive gut microenvironment have repeatedly emerged as causative pathophysiology in patients with irritable bowel syndrome (IBS). Our aim was to study these phenomena by comparing gut-related symptoms, psychological scores, and biopsy samples generated from a detailed diarrhea-predominant IBS patient (IBS-D) cohort before their entry into a previously reported clinical trial. METHODS: Data were generated from 42 patients with IBS-D who completed a daily 2-week bowel symptom diary, the Hospital Anxiety and Depression score, and the Patient Health Questionnaire-12 Somatic Symptom score and underwent unprepared flexible sigmoidoscopy. Sigmoid mucosal biopsies were separately evaluated using immunohistochemistry and culture supernatants to determine cellularity, mediator levels, and ability to stimulate colonic afferent activity. RESULTS: Pain severity scores significantly correlated with the daily duration of pain (r = 0.67, P < 0.00001), urgency (r = 0.57, P < 0.0005), and bloating (r = 0.39, P < 0.05), but not with psychological symptom scores for anxiety, depression, or somatization. Furthermore, pain severity scores from individual patients with IBS-D were significantly correlated (r = 0.40, P < 0.008) with stimulation of colonic afferent activation mediated by their biopsy supernatant, but not with biopsy cell counts nor measured mediator levels. DISCUSSION: Peripheral pronociceptive changes in the bowel seem more important than psychological factors in determining pain severity within a tightly phenotyped cohort of patients with IBS-D. No individual mediator was identified as the cause of this pronociceptive change, suggesting that nerve targeting therapeutic approaches may be more successful than mediator-driven approaches for the treatment of pain in IBS-D.